2022
DOI: 10.1093/bjsopen/zrac148
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of type 3c diabetes mellitus after acute pancreatitis warrants a personalized approach including diabetes screening

Abstract: Background Acute pancreatitis (AP) is a frequent cause of hospitalization with long-term health consequences, including type 3c diabetes mellitus (DM). The incidence and risk factors for new-onset morbidities after AP need to be clarified to inform a personalized medicine approach. Methods Using a longitudinal electronic healthcare record-linkage analysis, all patients admitted to hospital in Scotland with a first episode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Figure 7 displays the pooled OR for the remainder of the prognostic factors that were reported on by a sufficient number of included studies in a comparable manner for quantitative synthesis (see Supplementary Figures S11 – S22 for individual forest plots). We found that obesity ( 29 , 39 , 41 , 43 , 49 , 50 , 62 ) and chronic kidney disease ( 36 , 38 , 43 ) were associated with a significantly higher odds of developing DM (OR: 1.85; CI: 1.43–2.38 and OR: 2.10; CI: 1.85–2.38, respectively). We observed a statistically non-significant tendency of increased odds of developing DM with liver cirrhosis ( 20 , 38 , 63 ), other liver disease ( 37 , 43 , 64 ), dyslipidemia ( 20 , 37 , 42 , 43 ), and being overweight or obese ( 37 , 41 , 50 ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Figure 7 displays the pooled OR for the remainder of the prognostic factors that were reported on by a sufficient number of included studies in a comparable manner for quantitative synthesis (see Supplementary Figures S11 – S22 for individual forest plots). We found that obesity ( 29 , 39 , 41 , 43 , 49 , 50 , 62 ) and chronic kidney disease ( 36 , 38 , 43 ) were associated with a significantly higher odds of developing DM (OR: 1.85; CI: 1.43–2.38 and OR: 2.10; CI: 1.85–2.38, respectively). We observed a statistically non-significant tendency of increased odds of developing DM with liver cirrhosis ( 20 , 38 , 63 ), other liver disease ( 37 , 43 , 64 ), dyslipidemia ( 20 , 37 , 42 , 43 ), and being overweight or obese ( 37 , 41 , 50 ).…”
Section: Resultsmentioning
confidence: 84%
“…We found no association between new-onset DM and hypertension ( 20 , 36 , 37 , 43 ), cardiovascular disease ( 20 , 36–38 , 43 ), or age ( 20 , 38 , 43 ). Smoking ( 29 , 31 , 36–38 , 43 , 64–66 ), alcohol consumption ( 29 , 31 , 36 , 37 , 64 , 67 ), and male sex ( 20 , 27 , 31–33 , 35–38 , 41 , 42 , 47 , 50 , 61 , 62 , 68–70 ) were not associated with either new-onset DM or PD/DM.…”
Section: Resultsmentioning
confidence: 96%
“…SegundoMelki et al (2019) eWalker et al (2022) o tratamento do diabetes mellitus 3c tende a ser mais desafiador do que o do diabetes mellitus tipo 1 e 2 devido a uma variedade de características metabólicas, como baixos estoques de glicogênio e hemoglobina glicada normal. Os níveis de glucagon e insulina são baixos devido à destruição das células alfa e beta, respectivamente.…”
unclassified
“…Finally, the pancreas field has also seen some major publications in BJS Open in 2022. Of great interest, for a non-surgical readership also, is a paper focusing on the risk of type 3c diabetes mellitus after more than 2000 cases of acute pancreatitis followed for a minimum of 5 years after the index episode has been published 3 . The analysis underlines the current burden of long-term comorbidity after acute pancreatitis, particularly once this has required critical care, and calls for a personalized and multidisciplinary approach, including diabetes screening.…”
mentioning
confidence: 99%